ANALISIS INFLASI DI SUMATERA UTARA: SUATU MODEL ERROR CORRECTION (ECM) - Hafsyah Aprillia (Quantitative Economics Journal, 2012)
The research was conducted to determine the effect of economic variables that can explain the change or variation in the rate of inflation in the Consumer Price Index (CPI) as the dependent variable. The explanatory variables (independent) were used as controls are SBI, the nominal interest rate spread (SBI) and the value of the rupiah against the U.S. dollar. Based on these results, according to the specific purpose of the model equations II, suggested economic actors can use SBI interest rate spread as an indicator of variations in the CPI inflation rate at intervals of 8 and 12 months, with a note that the obtained level of explanation has not shown that the optimal value.